KEPENTINGAN NASIONAL AMERIKA SERIKAT MENYEPAKATI JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) TAHUN 2015 - Dwi Wahyuni, Ni Made; Susanti, Sukma; Nugraha, A.A. Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2018), 2018)
ABSTRACT Several sanctions by the United States and the European Union have not stopped Iran's action to continue its nuclear development program.A series of meetings by the P5 + 1 group conducted to solve the Iranian nuclear issue. The meeting resulted in a framework agreement called Joint Comprehensive Plan of Action (JCPOA). The aim of the agreement was to recognize Iran’s nuclear rights. This study is devoted to discuss US national interest on JCPOA agreement with Iran. In orde to answer the research question, this research uses qualitative method with secondary data source which then analyzed using national interest and US grand saretgy concept. The results of this study show the interests for security (vital interest) and interest of maintaining the world order (highly important interest) become the basis of consideration US policy agrees JCPOA greement. Keywords: United State of America, Nuclear, Iran, JCPOA